Small parts assembly with a dual-arm industrial robot for 3C industry applications – system design - Khoo, Daniel Wei Qian (2017)
This report shows the research and modifications done by the author on a dual-arm industrial NEXTAGE robot by KAWADA Industries for 3C industrial applications. First, it gives a brief introduction on industrial robots and possible applications in the 3C industry. Then, there will be a short description of the NEXTAGE Robot with details on its specifications. It later covers the add-ons and system development done by the previous team. The software development for NEXTAGE was done in Ubuntu 14.04 using the Indigo version of Robot Operating System (ROS). Existing methods that are used for object identification software development and path planning of the robot will be explained. Thirdly, it explains the use of ROS and how can it be implemented together with NEXTAGE and what are the challenges during implementation. The report will talk about the limitations of the current gripper and will list out the process of designing and selection of material for its new gripper tool for NEXTAGE to use in the 3C industry. The flaw of the design is thoroughly investigated and explained with a solution which is fabricating a new part with additional support material. The report ends with a conclusion on the reviews on the computer vision functions and path planning of the robot, feedback on the difficulties to implementing ROS together with NEXTAGE, design process and complications with the gripper and the robot’s future advancement into the 3C industry.